METHODS AND COMPOSITIONS RELATED TO GPCR AGONIST POLYPEPTIDES - LERNER RICHARD A; STURCHLER EMMANUEL; XIE JIA; ZHANG HONGKAI; MC DONALD PATRICIA (2018)
The invention provides combinatorial peptide or polypeptide libraries that can become membrane tethered once expressed in cells. The invention additionally provides methods for selecting peptide modulators (e.g., agonists) of GPCRs from the combinatorial libraries of the invention. The invention also provides novel GPCR polypeptide modulators, e.g., biased polypeptide agonists of the glucagon-likepeptide 1 receptor (GLP-1R). The invention further provides methods of promoting insulin sensitivity, lowering blood glucose, and reducing body weight as well as methods for treating various diseasessuch as diabetes and obesity. 本发明提供了在细胞中表达时会变成膜束缚的组合肽或多肽文库。本发明另外提供了用于从本发明的组合文库中选择GPCR的肽调节剂(例如激动剂)的方法。本发明还提供新型GPCR多肽调节剂，例如胰高血糖素样肽1受体(GLP-1R)的偏倚多肽激动剂。本发明还提供了促进胰岛素敏感性、降低血糖和降低体重的方法以及用于治疗如糖尿病和肥胖症等多种疾病的方法。